Foamable urethane resin composition and polyurethane foam
Patent Information
- Application Number
- JP2020208844
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-16
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2040-12-16
Smart Images

Figure 0007630268000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a foamable urethane resin composition and a polyurethane foam. [Background technology]
[0002] Polyurethane foams are used in practical applications for insulation and condensation prevention for ceilings, roofs, walls, etc. of buildings such as apartment complexes, detached houses, and commercial buildings, taking advantage of their excellent heat insulating properties. Although polyurethane foams are lightweight, they are organic and therefore flammable. In order to improve this, polyurethane foams containing flame retardants and the like to enhance flame retardancy are used. For example, Patent Document 1 describes a flame-retardant polyurethane foam obtained by using ammonium polyphosphate, a urea derivative, a polyol, and an isocyanate, characterized in that the flame-retardant polyurethane foam is obtained by using ammonium polyphosphate in the range of 5 to 150 parts by weight and a urea derivative in the range of 0.001 to 15 parts by weight per 100 parts by weight of polyol. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-151524 A Summary of the Invention [Problem to be solved by the invention]
[0004] In recent years, relatively many fires caused by polyurethane foams used as heat insulating materials in buildings have been reported. In order to improve such problems, it is expected that polyurethane foams that not only have excellent flame retardancy but also have the property of being difficult to spread when a fire breaks out are developed. In addition, when a polyurethane foam burns in the event of a fire, colored smoke such as black smoke is generated, which blocks the view of evacuees and causes breathing difficulties, making evacuation difficult. Therefore, it is expected that polyurethane foams that have the property of being difficult to generate smoke are developed. Therefore, an object of the present invention is to provide a foamable urethane resin composition for producing a polyurethane foam that has the property of being resistant to the spread of fire and the property of being resistant to the generation of smoke in the event of a fire, and a polyurethane foam. [Means for solving the problem]
[0005] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by a foamable urethane resin composition containing a polyol compound, a polyisocyanate compound, a flame retardant, a blowing agent, and a catalyst, which exhibits a specific value of total smoke release (TSR) when subjected to a cone calorie test in accordance with the ISO-5660 test method, and have completed the present invention. That is, the present invention provides the following [1] to [9]. [1] A foamable urethane resin composition comprising a polyol compound, a polyisocyanate compound, a flame retardant, a blowing agent, and a catalyst, the polyurethane foam comprising the foamable urethane resin composition having a total smoke emission of 500 m when subjected to a cone calorie test in accordance with the ISO-5660 test method. 2 / m 2 1. A foamable urethane resin composition comprising: [2] The foamable urethane resin composition according to [1], wherein the catalyst contains a trimerization catalyst. [3] The foamable urethane resin composition according to [1] or [2], wherein the polyol compound contains an aromatic polyester polyol, and the content of the aromatic polyester polyol is 50 parts by mass or more per 100 parts by mass of the polyol compound. [4] The foamable urethane resin composition according to any one of [1] to [3], which is substantially free of inorganic filler. [5] The foamable urethane resin composition according to any one of [1] to [3], wherein the foamable urethane resin composition contains an inorganic filler, and the inorganic filler is a brominated flame retardant. [6] The foamable urethane resin composition according to any one of [1] to [5], having an isocyanate index of 130 to 600. [7] The foamable urethane resin composition according to any one of [1] to [6], which is used for spray applications. [8] The foamable urethane resin composition according to any one of [1] to [7], wherein the catalyst contains a bismuth compound. [9] A polyurethane foam obtained by foaming the foamable urethane resin composition according to any one of [1] to [8]. Effect of the Invention
[0006] Effects of the Invention The present invention can provide a foamable urethane resin composition for producing a polyurethane foam that has the property of being resistant to the spread of fire and the property of being resistant to the generation of smoke in the event of a fire, etc., and a polyurethane foam. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] [Foamable urethane resin composition] The foamable urethane resin composition of the present invention contains a polyol compound, a polyisocyanate compound, a flame retardant, a foaming agent, and a catalyst. The composition and properties of the foamable urethane resin composition of the present invention will be described below.
[0008] (Polyol Compound) The polyol compound contained in the foamable urethane resin composition of the present invention is not particularly limited, but is preferably polyether polyol, polyester polyol, or bromine-containing polyol.Among them, aromatic polyester polyol is preferred, and phthalic acid polyester polyol is more preferred, as described below, from the viewpoint of increasing the flame retardancy of the obtained polyurethane foam and reducing the total amount of smoke generated to suppress the generation of smoke when a fire occurs.In addition, aromatic polyester polyol such as phthalic acid polyester polyol is preferably used alone as a polyol compound, but may be used in combination with other polyol compounds such as polyether polyol, as described below.
[0009] <Polyether polyol> Polyether polyol is a polyoxyalkylene polyol obtained by ring-opening addition polymerization of an alkylene oxide to an initiator having two or more active hydrogen atoms. Specific examples of the initiator include aliphatic polyhydric alcohols (e.g., glycols such as ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexylene glycol, and cyclohexanedimethanol, triols such as trimethylolpropane and glycerin, tetrafunctional alcohols such as pentaerythritol, and highly functional alcohols such as sucrose and sorbitol), aliphatic amines (e.g., alkylenediamines such as ethylenediamine, propylenediamine, butylenediamine, hexamethylenediamine, and neopentyldiamine, and alkanolamines such as monoethanolamine and diethanolamine), and aromatic amines (e.g., aniline, tolylenediamine, xylylenediamine, diphenylmethanediamine, and Mannich condensation products), and the like. These may be used alone or in combination of two or more.
[0010] As the polyether polyol, from the viewpoint of improving the moldability at the time of injection during urethane foaming and the workability at the time of spraying, tolylenediamine-based polyether polyol, Mannich-based polyether polyol, sucrose-based polyether polyol, sorbitol-based polyether polyol, and ethylenediamine-based polyether polyol are preferred. These polyether polyols may be used alone or in combination of two or more. Among the above, it is more preferred to use at least Mannich-based polyether polyol, and it is even more preferred to use both Mannich-based polyether polyol and ethylenediamine-based polyether polyol. These polyether polyols are preferably used in combination with aromatic polyester polyols described later from the viewpoint of achieving both moldability and flame retardancy, and from the viewpoint of lowering the total smoke emission and enhancing the low smoke property described later. The content of the polyether polyol is preferably 5 to 50 parts by mass, more preferably 10 to 40 parts by mass, per 100 parts by mass of the polyol compound, from the viewpoint of enhancing moldability, flame retardancy, and low smoke property. From such a viewpoint, in one embodiment of the present invention, the polyol compound of the present invention more preferably contains a polyether polyol and a phthalic acid-based polyester polyol described later. The type and content of the phthalic acid-based polyester polyol will be described later.
[0011] The tolylenediamine-based polyether polyol is a polyether polyol obtained by using tolylenediamine as an initiator. The same applies to sucrose-based polyether polyol, sorbitol-based polyether polyol, and ethylenediamine-based polyether polyol. The Mannich polyether polyol is a polyether polyol obtained by utilizing the Mannich reaction, which is a Mannich condensation product having two or more hydroxyl groups in the molecule, or an alkylene oxide added to such a Mannich condensation product. More specifically, it is a Mannich condensation product obtained by the Mannich reaction of at least one of phenol and its alkyl-substituted derivatives, formaldehyde and alkanolamine, or a polyether polyol obtained by ring-opening addition polymerization of at least one of ethylene oxide and propylene oxide to this compound.
[0012] The hydroxyl value of the polyether polyol is preferably from 200 to 1,000 mgKOH / g, more preferably from 250 to 800 mgKOH / g, and further preferably from 300 to 500 mgKOH / g. The hydroxyl value is a value measured in accordance with JIS K1557-1:2007.
[0013] <Polyester polyol> Examples of polyester polyols include aromatic polyester polyols and aliphatic polyester polyols, but when considering the flame retardancy of the resulting polyurethane foam, it is preferable to use aromatic polyester polyols. The aromatic polyester polyol is preferably a condensate of an aromatic dicarboxylic acid such as o-phthalic acid (phthalic acid), m-phthalic acid (isophthalic acid), p-phthalic acid (terephthalic acid), or naphthalenedicarboxylic acid with a glycol. Among them, from the viewpoint of increasing the flame retardancy of the polyurethane foam, decreasing the value of the steel ball sinking distance described above, and improving the flame-spreading performance, and from the viewpoint of suppressing the total amount of smoke and ensuring low smoke properties, it is preferable that the polyol compound contains a phthalic acid-based polyester polyol, which is a condensate of phthalic acid and a glycol, and more preferably contains a p-phthalic acid-based polyester polyol, which is a condensate of p-phthalic acid and a glycol. The glycol is not particularly limited, but it is preferable to use low molecular weight aliphatic glycols known as components of polyester polyols, such as ethylene glycol, propylene glycol, and diethylene glycol.
[0014] From the viewpoint of improving moldability, flame retardancy, and low smoke properties, the content of the aromatic polyester polyol is preferably 50 parts by mass or more, more preferably 70 parts by mass or more, even more preferably 90 parts by mass or more, and even more preferably 100 parts by mass, per 100 parts by mass of the polyol compound. As described above, the aromatic polyester polyol is preferably a phthalic acid-based polyester polyol, and therefore, an embodiment in which the content of the phthalic acid-based polyester polyol is within the above range is more preferable.
[0015] The hydroxyl value of the polyester polyol is preferably from 100 to 400 mgKOH / g, more preferably from 150 to 350 mgKOH / g, and further preferably from 170 to 280 mgKOH / g.
[0016] <Bromine-containing polyol> Examples of the bromine-containing polyol include aromatic bromine-containing polyol and aliphatic bromine-containing polyol. In the present invention, either one of them may be used, or both may be used in combination. From the viewpoint of improving flame retardancy, the bromine-containing polyol preferably contains an aromatic bromine-containing polyol. Examples of the aromatic bromine-containing polyol include aromatic bromine-containing polyester polyol and aromatic bromine-containing polyether polyol.
[0017] As the aromatic bromine-containing polyester polyol, for example, one obtained by an esterification reaction between a bromine-containing polycarboxylic acid such as tetrabromophthalic acid and a polyhydric alcohol can be used. Examples of polyhydric alcohols include ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, glycerin, trimethylolpropane, pentaerythritol, sorbitol, sucrose, and bisphenol A. These may be used alone or in appropriate combination of two or more.
[0018] The aromatic bromine-containing polyether polyol may be, for example, one obtained by addition polymerization of a bromine-containing polyhydric alcohol such as tetrabromobisphenol A with one or more alkylene oxides such as ethylene oxide, propylene oxide, butylene oxide, etc. When a bromine-containing polyether polyol is used, it is particularly preferable to use an aromatic bromine-containing polyether polyol having a tetrabromobisphenol A skeleton.
[0019] Examples of the aliphatic bromine-containing polyol include aliphatic bromine-containing polyether polyols and aliphatic bromine-containing polyester polyols. Among these, aliphatic bromine-containing polyether polyols are preferred.
[0020] The content of the bromine-containing polyol is preferably 14 to 100 parts by mass, and more preferably 20 to 90 parts by mass, per 100 parts by mass of the polyol compound, from the viewpoints of improving flame retardancy and resistance to flame spread and suppressing expansion and deformation upon heating.
[0021] The hydroxyl value of the bromine-containing polyol is preferably from 100 to 600 mgKOH / g, more preferably from 110 to 450 mgKOH / g, and further preferably from 110 to 350 mgKOH / g.
[0022] (Polyisocyanate compounds) As the polyisocyanate compound contained in the foamable urethane resin composition of the present invention, various polyisocyanate compounds having two or more isocyanate groups, such as aromatic, alicyclic and aliphatic polyisocyanate compounds, can be used.
[0023] Examples of aromatic polyisocyanates include phenylene diisocyanate, tolylene diisocyanate, diphenylmethane diisocyanate, dimethyldiphenylmethane diisocyanate, triphenylmethane triisocyanate, naphthalene diisocyanate, and polymethylene polyphenyl polyisocyanate (polymeric MDI).
[0024] Examples of the alicyclic polyisocyanate include cyclohexylene diisocyanate, methylcyclohexylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, and dimethyldicyclohexylmethane diisocyanate. Examples of the aliphatic polyisocyanate include methylene diisocyanate, ethylene diisocyanate, propylene diisocyanate, tetramethylene diisocyanate, and hexamethylene diisocyanate.
[0025] Among these, from the viewpoints of ease of handling, reaction speed, physical properties of the resulting polyurethane foam, and low cost, it is preferable to use aromatic polyisocyanates, and it is more preferable to use liquid diphenylmethane diisocyanate (MDI). Liquid MDI may be crude MDI (also called polymeric MDI). Specific commercial products of liquid MDI include "44V-10" and "44V-20" (manufactured by Sumika Covestro Urethane Co., Ltd.), "Millionate MR-200" (Nippon Polyurethane Industry Co., Ltd.), etc. Also, uretonimine-containing MDI (for example, a commercial product "Millionate MTL": manufactured by Nippon Polyurethane Industry Co., Ltd.) may be used. In addition to liquid MDI, other polyisocyanate compounds may be used in combination, and as the polyisocyanate compounds to be used in combination, polyisocyanate compounds known in the technical field of polyurethanes can be used without limitation. Also, a polyisocyanate in which some of the isocyanate active groups have been reacted with a hydroxyl group-containing compound to enhance affinity with polyols may be used.
[0026] Isocyanate Index The isocyanate index of the foamable urethane resin composition of the present invention is preferably in the range of 130 to 600, more preferably 150 to 550, and further preferably 230 to 500. When the isocyanate index is in such a range, the nurate ratio is high, which makes it easier to improve flame retardancy and flame spread resistance, and also makes it easier to suppress the total amount of smoke generated and thus suppress the generation of smoke in the event of a fire.
[0027] The isocyanate index (INDEX) is calculated as follows. INDEX = equivalents of isocyanate ÷ (equivalents of polyol + equivalents of water) × 100 Where: Isocyanate equivalent number = number of parts of polyisocyanate used x NCO content (%) x 100 / NCO molecular weight Polyol equivalent number = OHV × number of parts of polyol used ÷ molecular weight of KOH, OHV is the hydroxyl value of polyol (mgKOH / g), Equivalents of water = parts of water used × number of OH groups in water / molecular weight of water In the above formula, the unit of parts used is weight (g), the molecular weight of the NCO group is 42, the NCO content is the proportion of NCO groups in the polyisocyanate compound expressed as mass%, and for convenience of unit conversion in the above formula, the molecular weight of KOH is 56,100, the molecular weight of water is 18, and the number of OH groups in water is 2.
[0028] (Flame retardant) The foamable urethane resin composition of the present invention contains a flame retardant. The flame retardant used in the present invention preferably contains a phosphate ester-based flame retardant. By containing the phosphate ester-based flame retardant, the flame retardancy of the foamable urethane resin composition is improved. In addition, the phosphoric acid ester flame retardant is preferably a liquid flame retardant. The foamable urethane resin composition contains a liquid phosphoric acid ester flame retardant, so that the amount of solid flame retardant used can be reduced. Therefore, the storage stability of the composition is improved, sediment is less likely to occur during storage, and wear of the equipment used when the composition is used can be suppressed. Furthermore, smoke is less likely to be generated when a fire occurs while maintaining high flame retardancy. Furthermore, wear of the equipment used during use of the composition cannot be sufficiently suppressed. Here, room temperature means 23°C.
[0029] <Phosphate ester flame retardants> The phosphate flame retardant used in the present invention includes monophosphate, condensed phosphate, and the like. Examples of monophosphate esters include, but are not limited to, trimethyl phosphate, triethyl phosphate, tricresyl phosphate, cresyl diphenyl phosphate, trischloroethyl phosphate, and tris(β-chloropropyl) phosphate. The condensed phosphate ester is not particularly limited, but examples thereof include resorcinol polyphenyl phosphate (product name: CR-733S), bisphenol A polycresyl phosphate (product name: CR-741), aromatic condensed phosphate ester (product name: CR747) (product name: ADEKA PFR), and the like. Among the above, monophosphate esters are preferred, and monophosphate esters having chlorine atoms such as tris(β-chloropropyl)phosphate are more preferred. When a phosphate ester having chlorine atoms is used as the liquid flame retardant, the flame retardancy is easily improved. The content of the phosphate ester flame retardant is preferably 10 to 120 parts by mass, more preferably 15 to 100 parts by mass, further preferably 30 to 80 parts by mass, and even more preferably 35 to 70 parts by mass, relative to 100 parts by mass of the polyol compound. By setting the content of the phosphate ester flame retardant within the above range, it is possible to increase flame retardancy while reducing the total amount of smoke generated and suppressing smoke generation.
[0030] <Solid flame retardant> The flame retardant used in the present invention may include a solid flame retardant in addition to the above-mentioned phosphoric ester flame retardant. The solid flame retardant is a component contained as a solid in the foamable urethane resin composition and generally exists as a granular or powdered component. The solid flame retardant may be a component that is solid at room temperature (23°C) and normal pressure (1 atm) and does not dissolve in the foamable urethane resin composition. Preferred solid flame retardants include bromine-based flame retardants, boron-based flame retardants, phosphate-containing flame retardants, antimony-containing flame retardants, phosphinic acid-based flame retardants, expandable graphite, metal hydroxide-based flame retardants, red phosphorus, and needle-shaped fillers. Among these, bromine-based flame retardants are preferred from the viewpoints of improving the flame retardancy of the polyurethane foam and suppressing the total amount of smoke generated to improve the low smoke properties.
[0031] Brominated flame retardants The brominated flame retardant is not particularly limited as long as it is a compound containing bromine in its molecular structure, and examples thereof include aromatic brominated compounds. Specific examples of aromatic brominated compounds include monomeric organic bromine compounds such as hexabromobenzene, pentabromotoluene, hexabromobiphenyl, decabromobiphenyl, hexabromocyclodecane, decabromodiphenyl ether, octabromodiphenyl ether, hexabromodiphenyl ether, bis(pentabromophenoxy)ethane, ethylene bis(pentabromophenyl), ethylene bis(tetrabromophthalimide), and tetrabromobisphenol A; polycarbonate oligomers produced using brominated bisphenol A as a raw material; and mixtures of the polycarbonate oligomers and bisphenol A. Examples of suitable brominated epoxy compounds include brominated polycarbonates such as copolymers of brominated bisphenol A and epichlorohydrin, diepoxy compounds produced by the reaction of brominated bisphenol A with epichlorohydrin, and monoepoxy compounds obtained by the reaction of brominated phenols with epichlorohydrin, and halogenated bromine compound polymers such as poly(brominated benzyl acrylate), brominated polyphenylene ether, brominated bisphenol A, condensates of cyanuric chloride and brominated phenol, brominated (polystyrene), poly(brominated styrene), brominated polystyrene such as crosslinked brominated polystyrene, and crosslinked or non-crosslinked brominated poly(α-methylstyrene). Among these, monomeric organic bromine compounds are preferred, and ethylene bis(pentabromophenyl), ethylene bis(tetrabromophthalimide), hexabromobenzene, and the like are more preferred. The content of the brominated flame retardant is preferably from 5 to 80 parts by mass, more preferably from 10 to 60 parts by mass, and further preferably from 15 to 40 parts by mass, based on 100 parts by mass of the polyol compound.
[0032] Boron-based flame retardants Specific examples of the boron-based flame retardant include alkali metal borate such as lithium borate, sodium borate, potassium borate, and cesium borate, alkaline earth metal borate such as magnesium borate, calcium borate, and barium borate, zirconium borate, zinc borate, aluminum borate, and ammonium borate, etc. Among these, zinc borate is preferred. The content of the boron-based flame retardant is preferably from 5 to 80 parts by mass, more preferably from 10 to 60 parts by mass, and further preferably from 15 to 40 parts by mass, relative to 100 parts by mass of the polyol compound.
[0033] Phosphate-containing flame retardants Examples of phosphate-containing flame retardants include those containing phosphoric acid and a metal of Groups IA to IVB of the periodic table. At least one metal or compound selected from ammonia, aliphatic amines, and aromatic amines Examples of suitable salts include phosphates, which are salts with phosphates. The phosphoric acid is not particularly limited, but examples thereof include monophosphoric acid, pyrophosphoric acid, polyphosphoric acid, and the like. Can be obtained. Examples of metals in Groups IA to IVB of the periodic table include lithium, sodium, calcium, barium, iron (II), iron (III), aluminum, etc. Examples of the aliphatic amines include methylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, piperazine, etc. Examples of the aromatic amines include pyridine, triazine, melamine, etc. The above phosphate-containing flame retardants are treated with a silane coupling agent and coated with melamine resin. Alternatively, known water resistance improving treatments such as those described above may be applied.
[0034] Specific examples of phosphate-containing flame retardants include monophosphates, pyrophosphates, polyphosphates, and the like. The monophosphate is not particularly limited, but examples thereof include ammonium phosphate and dihydrate phosphoric acid. ammonium salts such as monobasic ammonium and diammonium hydrogen phosphate; monobasic sodium phosphate; Disodium phosphate, trisodium phosphate, monosodium phosphite, disodium phosphite sodium hypophosphite and other sodium salts, potassium phosphate monobasic, potassium phosphate dibasic, Potassium phosphate, tripotassium phosphite, dipotassium phosphite, potassium hypophosphite, etc. Lithium salts, monolithium phosphate, dilithium phosphate, trilithium phosphate, monolithium phosphite Lithium salts such as lithium diphosphite and lithium hypophosphite, barium dihydrogen phosphate, Barium salts such as barium hydrogen phosphate, barium triphosphate, and barium hypophosphate, Magnesium hydrogen, magnesium hydrogen phosphate, magnesium triphosphate, magnesium hypophosphite Magnesium salts of sodium, dihydrogen calcium phosphate, hydrogen calcium phosphate, trihydrogen calcium phosphate Calcium, calcium hypophosphite and other calcium salts, zinc phosphate, zinc phosphite, hypophosphite Examples include zinc salts such as zinc phosphate.
[0035] The polyphosphate is not particularly limited, but examples thereof include ammonium polyphosphate, piperazine polyphosphate, melamine polyphosphate, ammonium amide polyphosphate, and aluminum polyphosphate. The phosphate-containing flame retardants may be used alone or in combination of two or more. The content of the phosphate-containing flame retardant is preferably from 5 to 80 parts by mass, more preferably from 10 to 60 parts by mass, and even more preferably from 15 to 40 parts by mass, based on 100 parts by mass of the polyol compound.
[0036] Antimony-containing flame retardants Examples of the antimony-containing flame retardant used in the present invention include antimony oxide, antimonates, and pyroantimonates. Examples of antimony oxide include antimony trioxide and antimony pentoxide. Examples of antimonate include sodium antimonate and potassium antimonate. Examples of pyroantimonate include sodium pyroantimonate, Examples thereof include potassium pyroantimonate. Preferably, the antimony-containing flame retardant is antimony oxide. The antimony-containing flame retardants may be used alone or in combination of two or more. To further improve the flame retardancy, it is preferable to use it in combination with the above-mentioned bromine-based flame retardant. The content of the antimony-containing flame retardant is preferably from 5 to 80 parts by mass, more preferably from 10 to 60 parts by mass, and further preferably from 15 to 40 parts by mass, based on 100 parts by mass of the polyol compound.
[0037] Phosphinic acid flame retardants Examples of phosphinic acid flame retardants include phosphinic acid, dimethylphosphinic acid, methylethylphosphinic acid, methylpropylphosphinic acid, diethylphosphinic acid, dioctylphosphinic acid, phenylphosphinic acid, diethylphenylphosphinic acid, diphenylphosphinic acid, and bis(4-methoxyphenyl)phosphinic acid. The content of the phosphinic acid flame retardant is preferably from 5 to 80 parts by mass, more preferably from 10 to 60 parts by mass, and further preferably from 15 to 40 parts by mass, based on 100 parts by mass of the polyol compound.
[0038] Expanded graphite Expanded graphite is a type of crystalline compound that is produced by treating powders of natural flaky graphite, pyrolytic graphite, kish graphite, or the like with an inorganic acid and a strong oxidizing agent to generate a graphite intercalation compound, and that maintains the layered structure of carbon. Examples of inorganic acids include concentrated sulfuric acid, nitric acid, and selenic acid. Examples of strong oxidizing agents include concentrated nitric acid, persulfates, perchloric acid, perchlorates, permanganates, dichromates, dichromates, and hydrogen peroxide. The expanded graphite obtained by the acid treatment as described above may be further neutralized with ammonia, aliphatic lower amines, alkali metal compounds, alkaline earth metal compounds, and the like. The content of the expanded graphite is preferably from 20 to 150 parts by mass, more preferably from 30 to 120 parts by mass, and further preferably from 40 to 100 parts by mass, relative to 100 parts by mass of the polyol compound.
[0039] Metal hydroxide flame retardants Examples of metal hydroxide flame retardants include magnesium hydroxide, calcium hydroxide, aluminum hydroxide, iron hydroxide, nickel hydroxide, zirconium hydroxide, titanium hydroxide, zinc hydroxide, copper hydroxide, vanadium hydroxide, tin hydroxide, etc. The metal hydroxide flame retardants may be used alone or in combination of two or more. The content of the metal hydroxide flame retardant is preferably from 5 to 80 parts by mass, more preferably from 10 to 60 parts by mass, and further preferably from 15 to 40 parts by mass, based on 100 parts by mass of the polyol compound.
[0040] 《Red phosphorus》 The red phosphorus may be made of simple red phosphorus, or may be red phosphorus mixed with or coated with a resin, a metal hydroxide, a metal oxide, or the like. The content of red phosphorus is preferably from 3 to 60 parts by mass, more preferably from 5 to 50 parts by mass, and further preferably from 10 to 40 parts by mass, based on 100 parts by mass of the polyol compound.
[0041] Needle-shaped filler Examples of needle-like fillers include potassium titanate whiskers, aluminum borate whiskers, magnesium-containing whiskers, silicon-containing whiskers, wollastonite, sepiolite, zonolite, elestadite, boehmite, rod-shaped hydroxyapatite, glass fibers, carbon fibers, graphite fibers, metal fibers, slag fibers, gypsum fibers, silica fibers, alumina fibers, silica alumina fibers, zirconia fibers, boron nitride fibers, boron fibers, and stainless steel fibers. These needle-like fillers can be used alone or in combination of two or more. The content of the needle filler is preferably from 20 to 100 parts by mass, more preferably from 30 to 90 parts by mass, and further preferably from 40 to 80 parts by mass, based on 100 parts by mass of the polyol compound.
[0042] The content of the solid flame retardant is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, based on 100 parts by mass of the polyol compound. If the content of the solid flame retardant is equal to or more than these lower limits, the concentration of the polyol compound in the polyol composition decreases, so that when the polyol composition and the polyisocyanate composition are mixed at a certain volume ratio as described above, the isocyanate index tends to increase, and therefore the flame retardancy of the resulting polyurethane foam is improved. In addition, when a solid flame retardant is used, the function of the solid flame retardant itself can improve the flame retardancy. The content of the solid flame retardant is preferably 80 parts by mass or less, more preferably 60 parts by mass or less, and even more preferably 50 parts by mass or less, based on 100 parts by mass of the polyol compound. When the content of the solid flame retardant is equal to or less than these upper limits, clogging of the spraying device is suppressed, and spraying properties can be improved.
[0043] (foaming agent) The foamable urethane resin composition of the present invention contains a foaming agent. Specific examples of the foaming agent include water, low-boiling point hydrocarbons, chlorinated aliphatic hydrocarbon compounds, fluorine compounds, hydrochlorofluorocarbon compounds, hydrofluorocarbons, ether compounds, and hydrofluoroolefins. Further, examples of the foaming agent include organic physical foaming agents such as mixtures of these compounds, and inorganic physical foaming agents such as nitrogen gas, oxygen gas, argon gas, and carbon dioxide gas. Examples of the low boiling point hydrocarbon include propane, butane, pentane, hexane, heptane, cyclopropane, cyclobutane, cyclopentane, cyclohexane, and cycloheptane. Examples of the chlorinated aliphatic hydrocarbon compounds include dichloroethane, propyl chloride, isopropyl chloride, butyl chloride, isobutyl chloride, pentyl chloride, and isopentyl chloride. Examples of the fluorine compound include CHF3, CH2F2, and CH3F. Examples of the hydrochlorofluorocarbon compounds include trichloromonofluoromethane, trichlorotrifluoroethane, and dichloromonofluoroethane (for example, HCFC141b (1,1-dichloro-1-fluoroethane), HCFC22 (chlorodifluoromethane), and HCFC142b (1-chloro-1,1-difluoroethane)). Examples of the hydrofluorocarbon include HFC-245fa (1,1,1,3,3-pentafluoropropane) and HFC-365mfc (1,1,1,3,3-pentafluorobutane). The ether compound may, for example, be diisopropyl ether. Examples of the hydrofluoroolefin include HFO-1233zd(E) (trans-1-chloro-3,3,3-trifluoropropene), HFO-1234yf (2,3,3,3-tetrafluoro-1-propene), HFO-1336mzz(Z) (cis-1,1,1,4,4,4,-hexafluorobut-2-ene), and HFO-1224yd(Z).
[0044] In the present invention, the blowing agent preferably contains water, and more specifically, a blowing agent containing at least one compound selected from the above-mentioned low-boiling point hydrocarbons, chlorinated aliphatic hydrocarbon compounds, fluorine compounds, hydrochlorofluorocarbon compounds, hydrofluorocarbons, ether compounds, and hydrofluoroolefins in combination with water is preferred. As the water, for example, ion-exchanged water, distilled water, etc. can be appropriately used. The amount of water relative to 100 parts by mass of the polyol compound is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and preferably 2.0 parts by mass or less, more preferably 1.5 parts by mass or less, and even more preferably 1.1 parts by mass or less. When the content of water is equal to or more than these lower limits, the foamable urethane resin composition is easily foamed. Also, when the content of water is equal to or less than these upper limits, the flame retardancy is improved, and the total amount of smoke is suppressed to ensure low smoke while ensuring the property of being difficult to spread flames.
[0045] In the present invention, the foaming agent preferably contains a hydrofluoroolefin, and more preferably contains both the hydrofluoroolefin and the above-mentioned water. The amount of the hydrofluoroolefin relative to 100 parts by mass of the polyol compound is preferably 10 to 60 parts by mass, more preferably 15 to 55 parts by mass, even more preferably 20 to 50 parts by mass, and even more preferably 28 to 40 parts by mass.
[0046] (catalyst) The foamable urethane resin composition of the present invention contains a catalyst. The catalyst may contain, for example, one or both of a urethanization catalyst and a trimerization catalyst, and preferably contains both. It should be noted that the catalyst contained in the foamable urethane resin composition does not fall under the category of the inorganic filler in the present invention.
[0047] The urethane catalyst is a catalyst that promotes the reaction between the polyol component and the polyisocyanate.Specific examples include bismuth compounds, amino compounds, tin compounds, and acetylacetone metal salts.Among these, bismuth compounds are preferred from the viewpoint of increasing initial activity without decreasing flame retardancy or storage stability when used for spraying purposes. Examples of bismuth compounds include bismuth 2-ethylhexanoate, bismuth neodecanoate, and bismuth octoate. Examples of the amino compound include pentamethyldiethylenetriamine, triethylamine, N-methylmorpholine bis(2-dimethylaminoethyl)ether, bis(2-dimethylaminoethyl)ether, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N'-trimethylaminoethyl-ethanolamine, bis(2-dimethylaminoethyl)ether, N-methyl-N',N'-dimethylaminoethylpiperazine, imidazole compounds in which the secondary amine functional group in the imidazole ring is substituted with a cyanoethyl group, N,N-dimethylcyclohexylamine, diazabicycloundecene, triethylenediamine, tetramethylethylenediamine, tetramethylhexamethylenediamine, 1-methylimidazole, 1,2-dimethylimidazole, trimethylaminoethylpiperazine, and tripropylamine. As the amino compound, an imidazole compound is preferable. Examples of the tin compound include stannous octoate, dibutyltin diacetate, and dibutyltin dilaurate. Examples of acetylacetone metal salts include acetylacetone aluminum, acetylacetone iron, acetylacetone copper, acetylacetone zinc, acetylacetone beryllium, acetylacetone chromium, acetylacetone indium, acetylacetone manganese, acetylacetone molybdenum, acetylacetone titanium, acetylacetone cobalt, acetylacetone vanadium, and acetylacetone zirconium. The urethanization catalyst may be used alone or in combination of two or more kinds.
[0048] The amount of the urethane catalyst in the foamable urethane resin composition is not particularly limited, but is preferably in the range of 1 to 25 parts by mass, more preferably in the range of 1.5 to 20 parts by mass, and even more preferably in the range of 2 to 15 parts by mass, relative to 100 parts by mass of the polyol compound. By keeping the amount within the above range, the reaction between the polyol compound and the polyisocyanate compound can be promoted at an appropriate reaction rate.
[0049] As the urethane-forming catalyst, it is preferable to use a bismuth compound as described above, and the amount of the bismuth compound is preferably in the range of 0.05 to 13 parts by mass, more preferably in the range of 0.08 to 10 parts by mass, and even more preferably in the range of 0.1 to 8 parts by mass, relative to 100 parts by mass of the polyol compound. The bismuth compound is also preferably used in combination with an imidazole compound. When the bismuth compound and the imidazole compound are used in combination, the amount of the imidazole compound is preferably in the range of 1 to 12 parts by mass, more preferably in the range of 1.5 to 10 parts by mass, and further preferably in the range of 2 to 7 parts by mass, relative to 100 parts by mass of the polyol compound.
[0050] A trimerization catalyst is a catalyst that promotes trimerization to form an isocyanurate bond. By promoting trimerization of a polyurethane resin, the flame retardancy of a polyurethane foam is improved. As the trimerization catalyst, aromatic compounds such as tris(dimethylaminomethyl)phenol, 2,4-bis(dimethylaminomethyl)phenol, 2,4,6-tris(dialkylaminoalkyl)hexahydro-S-triazine, alkali metal salts such as potassium acetate, sodium acetate, potassium 2-ethylhexanoate, sodium 2-ethylhexanoate, potassium octylate, sodium octylate, aziridines such as 2-ethylaziridine, lead compounds such as lead naphthenate and lead octylate, alcoholates such as sodium methoxide, phenolates such as potassium phenoxide, tertiary ammonium salts such as trimethylammonium salts, triethylammonium salts, triphenylammonium salts, quaternary ammonium salts such as tetramethylammonium salts, tetraethylammonium, tetraphenylammonium salts, etc. can be used. Among these, quaternary ammonium salts are preferred. The trimerization catalyst may be used alone or in combination of two or more kinds.
[0051] The amount of the trimerization catalyst is not particularly limited, but is preferably in the range of 0.5 to 13 parts by mass, more preferably in the range of 1 to 10 parts by mass, and even more preferably in the range of 1.5 to 8 parts by mass, relative to 100 parts by mass of the polyol compound. By setting the amount of the trimerization catalyst within the above range, isocyanurate bonds are appropriately formed, and flame retardancy is improved. The total amount of the catalyst is preferably 1 to 38 parts by mass, more preferably 2 to 30 parts by mass, and even more preferably 3 to 23 parts by mass, per 100 parts by mass of the polyol compound, from the viewpoint of improving the urethane curing speed and flame retardancy.
[0052] (Inorganic filler) The foamable urethane resin composition of the present invention may contain an inorganic filler such as the solid flame retardant described above, but it is also preferable that the composition does not substantially contain an inorganic filler. By substantially not containing an inorganic filler, precipitation is unlikely to occur during storage, and re-stirring before use is not necessary. In addition, wear of the equipment used in spraying applications can be suppressed. Here, substantially no inorganic filler means that the content of inorganic filler is 5% by mass or less, and preferably 1% by mass or less, based on the total amount of the foamable urethane resin composition.
[0053] The inorganic filler is a particulate inorganic compound, and examples of the inorganic filler include a solid flame retardant, an inorganic filler other than a solid flame retardant, etc. The details of the solid flame retardant are as described above. In addition, examples of inorganic fillers other than solid flame retardants include silica, diatomaceous earth, alumina, titanium oxide, calcium oxide, magnesium oxide, iron oxide, tin oxide, antimony oxide, ferrites, basic magnesium carbonate, calcium carbonate, magnesium carbonate, barium carbonate, dawsonite, hydrotalcite, calcium sulfate, barium sulfate, potassium salts of calcium silicate, talc, clay, mica, montmorillonite, bentonite, activated clay, sepiolite, imogolite, sericite, glass beads, silica paln, aluminum nitride, boron nitride, silicon nitride, carbon black, graphite, carbon paln, charcoal powder, various metal powders, potassium titanate, magnesium sulfate, lead zirconate titanate, aluminum borate, molybdenum sulfide, silicon carbide, various magnetic powders, and fly ash.
[0054] (Foam stabilizer) The foamable urethane resin composition of the present invention may contain a foam stabilizer as required. Examples of the foam stabilizer include polyoxyalkylene foam stabilizers such as polyoxyalkylene alkyl ethers, and surfactants such as silicone foam stabilizers such as organopolysiloxanes, but the above types are not essential since any surfactant can be obtained as long as it has a structure that has polar and non-polar parts in the molecule. In addition, the silicone foam stabilizer may contain a graft copolymer of polydimethylsiloxane and polyethylene glycol. The content of the foam stabilizer is preferably 0.01 to 10 parts by mass, more preferably 0.1 to 8 parts by mass, and even more preferably 0.5 to 5 parts by mass, relative to 100 parts by mass of the polyol compound. The foam stabilizer may be used alone or in combination of two or more kinds.
[0055] (Other additives) The foamable urethane resin composition can contain, as additives, for example, phenol-based, amine-based, sulfur-based and other antioxidants, heat and light stabilizers, metal damage inhibitors, antistatic agents, crosslinking agents, lubricants, softeners, pigments, dyes, tackifying resins, and the like, within the scope of not impairing the effects of the present invention.
[0056] (Total Smoke Release (TSR)) The polyurethane foam made of the foamable urethane resin composition of the present invention was subjected to a cone calorie test in accordance with the test method of ISO-5660, and the total smoke emission was 500m 2 / m 2 The total smoke volume is less than 500m 2 / m 2 If the polyurethane foam is burned, a large amount of colored smoke such as black smoke will be generated, which may block the view of evacuees or cause breathing difficulties, making evacuation difficult. From the viewpoint of providing excellent low smoke properties to the polyurethane foam made of the foamable urethane resin composition of the present invention, the total smoke emission amount is set to be 500 m 2 / m 2 Preferably less than 300m 2 / m 2 It is more preferable that it is less than 200m. 2 / m 2 It is even more preferable that:
[0057] A specific example of a method for calculating the total smoke emission rate of a polyurethane foam made from the foamable urethane resin composition of the present invention is shown below. Note that the total smoke emission rate (TSR) [m 2 / m 2 ] may be automatically calculated and recorded. First, a cone calorimeter tester is used to record the change in smoke density of the smoke generated from the polyurethane foam, and the smoke production rate (SPR) is determined from the data. Smoke rate (SPR) [m 2 / s]=Smoke concentration[1 / m]×volume flow rate[m 3 / s] Next, the integrated value (TSP) of the obtained smoke rate (SPR) [m 2 ] is calculated. The unit area of the sample [m 2 Total smoke release rate (TSR) per unit [m 2 / m 2 ] is calculated.
[0058] The total smoke amount can be adjusted to a desired value by adjusting the type of polyol compound contained in the foamable urethane resin composition, the content of the flame retardant and water, the type and content of the catalyst, the isocyanate index, the presence or absence of a filler, the amount of the filler, the type of the filler, etc. For example, when the expression of flame retardancy is low due to a reason such as a small amount of the flame retardant despite the inclusion of a filler that promotes solid-phase flame retardancy such as char formation among the above solid flame retardants, the total smoke amount generally tends to be high, but when a specific filler such as a brominated flame retardant that has an effect on flame retardancy other than char formation is used or used in combination, the total smoke amount does not increase too much, and the total smoke amount can be suppressed even while using a filler.
[0059] (Total heat generation) The polyurethane foam made of the foamable urethane resin composition of the present invention was subjected to a test for a radiation heat intensity of 50 kW / m according to the ISO-5660 test method. 2 When heated for 5 minutes, the total heat generated is 10MJ / m 2 The total calorific value is preferably 10 MJ / m or less. 2 The polyurethane foam made of the foamable urethane resin composition of the present invention has a predetermined flame retardancy by satisfying the following: When the polyurethane foam has a predetermined flame retardancy and the steel ball sinking distance shown below is equal to or less than a certain value, the polyurethane foam has both flame retardancy and the property of not spreading fire, and can more effectively prevent the spread of fire in the event of a fire. From the viewpoint of further improving the flame retardancy of the polyurethane foam, the total calorific value is set to 9.5 MJ / m 2 More preferably, it is 9.0 MJ / m or less. 2 It is even more preferable that:
[0060] (Maximum heat generation rate) The polyurethane foam made of the foamable urethane resin composition of the present invention was subjected to a test for a radiation heat intensity of 50 kW / m according to the ISO-5660 test method. 2 The maximum heat generation rate when heated for 5 minutes is 150kW / m 2 It is preferable that the maximum heat generation rate is 150 kW / m or less.2 The polyurethane foam made of the foamable urethane resin composition of the present invention has a predetermined flame retardancy by being as described below. In addition, by adjusting both the maximum heat release rate and the total heat release amount as described above, the flame retardancy is further improved. By having a specified flame retardancy and having the steel ball sinking distance shown below be equal to or less than a certain value, the polyurethane foam has both flame retardancy and the property of not spreading fire, and can more effectively prevent the spread of fire in the event of a fire. From the viewpoint of further improving the flame retardancy of the polyurethane foam, the maximum heat generation rate is set to 140 kW / m 2 More preferably, it is 130 kW / m or less. 2 It is even more preferable that:
[0061] The total amount of smoke generated, the total amount of heat generated and the maximum heat release rate are obtained by a cone calorimeter test, and specifically, can be measured by the method described in the Examples. In the above-mentioned cone calorimeter test, it is preferable that the polyurethane foam used in the test has a shape stability to such an extent that it does not come into contact with the spark igniter of the cone calorimeter.
[0062] (Hot steel ball evaluation) The polyurethane foam made of the foamable urethane resin composition of the present invention preferably has a steel ball sinking distance of 12 mm or less in a hot steel ball test. By having a steel ball sinking distance of 12 mm or less, the polyurethane foam is less susceptible to fire spread when exposed to a fire, etc., and the spread of fire can be more effectively prevented. From the viewpoint of effectively preventing the spread of fire, the steel ball sinking distance is more preferably 10 mm or less, even more preferably 5 mm or less, and even more preferably 0 mm. The hot steel ball evaluation may be carried out according to the procedure described in the Examples.
[0063] The steel ball sinking distance in the above-mentioned hot steel ball evaluation can be adjusted to a desired value by adjusting the type of polyol compound contained in the foamable urethane resin composition, the content of flame retardant and water, the type and content of catalyst, the isocyanate index, etc.
[0064] In the hot steel ball evaluation, a cavity is formed in the test specimen from the top surface to the inside due to the sinking of the steel ball. The sinking distance of the steel ball means the maximum distance of the cavity in the vertical direction to the top surface of the test specimen. Note that parts that have discolored due to heat but retain their shape are not included in the measurement of the sinking distance.
[0065] (Vertical Burning Evaluation) The polyurethane foam made of the foamable urethane resin composition of the present invention is preferably one in which the flame reach distance in the flame spread state in the vertical combustion evaluation is 100 mm or less. When the flame spread state is 100 mm or less, the polyurethane foam is less likely to spread when exposed to a fire or the like, and the spread of the fire can be effectively prevented. From the viewpoint of effectively preventing the spread of the fire, the flame spread state is more preferably 75 mm or less, and even more preferably 50 mm or less. The vertical combustion evaluation may be performed according to the procedure described in the examples.
[0066] The total heat generation amount, maximum heat generation rate, steel ball sinking distance in the hot steel ball evaluation, and flame penetration distance in the vertical combustion evaluation of a polyurethane foam formed from the foamable urethane resin composition are measured by producing a polyurethane foam from the foamable urethane resin composition under conditions described in the examples.
[0067] The foamable urethane resin composition of the present invention is cured by the reaction of the polyol compound and the polyisocyanate compound, and therefore the viscosity of the composition changes with time. Therefore, before using the foamable urethane resin composition, the foamable urethane resin composition is divided into two or more portions to prevent the foamable urethane resin composition from reacting and curing. When using the foamable urethane resin composition, it is preferable to combine the two or more portions of the foamable urethane resin composition into one.
[0068] When the foamable urethane resin composition is divided into two or more components, each of the components of the foamable urethane resin composition divided into two or more components does not start curing alone, and each component may be divided so that the curing reaction starts after each component of the foamable urethane resin composition is mixed. Usually, the foamable urethane resin composition is divided into a polyol composition containing a polyol compound and a polyisocyanate composition containing a polyisocyanate compound.
[0069] The flame retardant, the blowing agent, the catalyst, and the foam stabilizer that is blended as necessary may be contained in the polyol composition, may be contained in the polyisocyanate composition, or may be provided separately from the polyol composition and the polyisocyanate composition, but are preferably contained in the polyol composition.
[0070] The method for producing the foamable urethane resin composition is not particularly limited, and examples thereof include a method in which a polyol composition and a polyisocyanate composition are prepared by kneading in advance and then mixed together, and a method in which each component constituting the foamable urethane resin composition is kneaded together, but the foamable urethane resin composition is usually produced by mixing a polyol composition and a polyisocyanate composition. The mixing of each component can be performed by a known method, and can be obtained by using a known device such as a high-pressure foaming machine, a low-pressure foaming machine, a spray foaming machine, or a hand mixer.
[0071] (Application) The use of the foamable urethane resin composition of the present invention is not particularly limited, and it can be used for filling cavities in structures such as buildings, furniture, automobiles, trains, ships, etc., or for spraying onto such structures. Among these, it is preferable to use it for spraying onto structures, i.e., as a foamable urethane resin composition for spraying. Spraying can be performed using a spraying device (e.g., A-25 manufactured by GRACO) and a spray gun (e.g., D-gun manufactured by Gasmar). A general spraying device and a spray gun spray the foaming liquid by reacting the isocyanate and polyol in an even volume ratio, so that the foaming liquid can be reacted in a volume ratio of 1.0 isocyanate to 0.8 to 1.2 polyol. Spraying can be performed by adjusting the temperature of a polyol composition and a polyisocyanate composition in separate containers in a spraying device, colliding and mixing the two at the tip of a spray gun, and turning the mixed liquid into mist by air pressure. The spraying device and the spray gun are known, and commercially available products can be used.
[0072] [Polyurethane foam] The polyurethane foam of the present invention is formed from the above-mentioned foamable urethane resin composition, specifically, is obtained by foaming and curing the foamable urethane resin composition.
[0073] The polyurethane foam of the present invention has a total smoke emission of 500 m when subjected to a cone calorie test in accordance with the ISO-5660 test method. 2 / m 2 Less than 300m 2 / m 2 Preferably less than 200m 2 / m 2 It is more preferable that: The polyurethane foam of the present invention also has the above-mentioned total heat release amount, maximum heat release rate, sinking distance in the hot steel ball evaluation, and flame penetration distance in the vertical combustion evaluation. EXAMPLES
[0074] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples in any way.
[0075] Details of each component used in each example and comparative example are as follows.
[0076] [Polyol Compound] p-Phthalic acid-based polyester polyol (Kawasaki Chemical Industries, Ltd., product name: RFK-509, hydroxyl value = 200 mg KOH / g) p-Phthalic acid-based polyester polyol (Kawasaki Chemical Industries, Ltd., product name: Maximol RLK-087, hydroxyl value = 200 mg KOH / g) p-Phthalic acid-based polyester polyol (Kawasaki Chemical Industries, Ltd., product name: Maximol RFK-505, hydroxyl value = 250 mg KOH / g) Mannich polyether polyol (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., product name: DK-3776, hydroxyl value = 350 mg KOH / g) Sucrose-based polyether polyol (manufactured by Mitsui Takeda Polychemicals, product name: GR-84, hydroxyl value 450 mg KOH / g) Ethylenediamine polyether polyol (AGC, product name: Exenol 750ED, hydroxyl value = 750 mg KOH / g)
[0077] 〔catalyst〕 (1) Trimerization catalyst Quaternary ammonium salt (manufactured by Evonik Japan, product name: TMR-7), mixture with ethylene glycol (concentration 45-55% by mass) (2) Urethane catalyst Imidazole compound <1,2-dimethylimidazole> (amino compound: manufactured by Kao Corporation, product name: Kao Raiser No. 390, concentration 65-75% by mass) Bismuth compound <Bismuth 2-ethylhexanoate> (Urethane metal catalyst: manufactured by Nitto Kasei Co., Ltd., product name: Bi28, concentration 81-90% by mass)
[0078] [Flame retardant] Phosphate ester flame retardant <Tris(β-chloropropyl)phosphate> (manufactured by Daihachi Chemical Industry Co., Ltd., product name: TMCPP) Solid flame retardant (bromine-based flame retardant) <Hexabromobenzene> (Manac Corporation, product name: HBB-B) Solid flame retardant (bromine-based flame retardant) <Ethylene-1,2-bis(pentabromophenyl)> (manufactured by Albemarle Corporation, product name: SAYTEX8010)
[0079] [Foaming Agent] ·water HFO-1233zd <hydrofluoroolefin> (Honeywell product name: Solstice LBA)
[0080] [Foam stabilizer] Silicone foam stabilizer (Toray Dow Corning, product name: SH-193)
[0081] [Polyisocyanate Compound] MDI (manufactured by Sumika Covestro Urethane Co., Ltd., product name: 44V-20)
[0082] The methods for measuring the various physical properties and characteristics are as follows.
[0083] [Total Smoke Release (TSR)] The total smoke release rate (TSR) of the polyurethane foams prepared in each Example and Comparative Example was evaluated by the following method. In a polypropylene beaker, a mixture obtained by mixing a polyol compound, a catalyst, a flame retardant, a foaming agent, and a foam stabilizer according to the formulation shown in Table 1 and a polyisocyanate compound (total amount 200 g, liquid temperature 10°C) were added and stirred for 3 seconds with a lab-di-spar. Immediately thereafter, the mixture was spread on a gypsum board with a thickness of 12.5 mm to obtain a polyurethane foam. The polyurethane foam adhered to the gypsum board as a base was cut into a length of 10 cm, a width of 10 cm, and a thickness of 3.25 cm (including a gypsum board of 12.5 mm) to prepare a sample for a cone calorimeter test, and a cone calorimeter test was performed as follows. The test sample was subjected to a cone calorimeter test in accordance with the test method of ISO-5660, and the total smoke release rate was measured. In addition to the above method, the polyurethane foam was also prepared by spraying a foamable urethane resin composition onto a structure using a spraying device and a spray gun, and similar values were obtained. The low smoke property of the resulting polyurethane foam was evaluated based on the total amount of smoke generated, as follows.
[0084] <Total smoke generation evaluation criteria> A Total smoke emission is 200m 2 / m 2 below B. The total smoke volume is 200m 2 / m 2 Super 300m 2 / m 2 below C Total smoke emission is 300m 2 / m 2 Super 500m 2 / m 2 below D Total smoke emission is 500m 2 / m 2 super
[0085] [Total heat generation, maximum heat generation rate] The total heat generation amount and maximum heat generation rate of the polyurethane foams produced in each of the Examples and Comparative Examples were evaluated by the following method. A mixture obtained by mixing a polyol compound, a catalyst, a flame retardant, a foaming agent, and a foam stabilizer in the formulation shown in Table 1 and a polyisocyanate compound (total amount 200 g, liquid temperature 10°C) were added to a polypropylene beaker and stirred for 3 seconds with a lab-di-spar. Immediately after that, the mixture was spread on a gypsum board with a thickness of 12.5 mm to obtain a polyurethane foam. The polyurethane foam adhered to the gypsum board as a base was cut into a length of 10 cm, a width of 10 cm, and a thickness of 3.25 cm (including gypsum board of 12.5 mm) to prepare a sample for a cone calorimeter test, and a cone calorimeter test was performed as follows. The test sample was measured in accordance with the ISO-5660 test method at a radiant heat intensity of 50 kW / m 2 The total heat release amount and maximum heat release rate were measured when the polyurethane foam was heated for 5 minutes at 40° C. In addition to the above-mentioned method, the polyurethane foam was also produced by spraying the foamable urethane resin composition onto a structure using a spraying device and a spray gun, and similar values were obtained.
[0086] [Corn calorie rating] The polyurethane foams produced in the respective Examples and Comparative Examples were evaluated by a cone calorimeter test.
[0087] <Corn calorie evaluation standard> A Total calorific value is 5 MJ / m 2 below B Total calorific value is 5 MJ / m 2 Super 8MJ / m 2 below C Total calorific value is 8 MJ / m 2 Super 10MJ / m 2 below D Total calorific value is 10 MJ / m 2 super
[0088] [Workability] The workability in producing a polyurethane foam from the polyol composition and the polyisocyanate composition prepared in each of the Examples and Comparative Examples was evaluated.
[0089] <Workability evaluation criteria> A. No need to remix the polyol composition and polyisocyanate composition when foaming them 24 hours after production B. The polyol composition and polyisocyanate composition need to be remixed when foaming 24 hours after production.
[0090] [Hot steel ball evaluation] For the polyurethane foams produced in each of the Examples and Comparative Examples, the sinking distance and fusion diameter distance of the steel ball were measured by the following procedures (1) to (3). (1) The polyurethane foam is cut into a rectangular prism with each side dimension of 100 mm x 100 mm x 60 mm to be used as the test specimen. (2) A steel ball with a diameter of 10.0 mm and a weight of 4.15 g was placed in an electric furnace set to a temperature of 800°C, and left for 10 minutes or more until the entire steel ball was heated uniformly and turned red, and the temperature of the steel ball was 800°C. Note that new steel balls were used. (3) In an atmosphere of 23°C, the steel ball heated in (2) above is immediately placed on the center of the upper part of the test piece in (1) above and left there until the steel ball has completely sunk in. Next, the cross section of the test piece that has been sufficiently cooled is cut and the sinking distance of the steel ball is measured. In this hot steel ball evaluation, the time from heating the steel ball to placing it on the test piece is within 1 second. The steel ball used is made of SUS304. Regarding the electric furnace, for example, a small programmable electric furnace (product name: MMF-1, manufactured by AS ONE Corporation) with inner dimensions of 120 mm×150 mm×100 mm was used. From the sinking distance of the steel ball obtained by the above procedure, the quality of the flame-proofing property was judged as follows.
[0091] <Hot steel ball evaluation criteria> A: The steel ball sinks below 5 mm B: The steel ball sinks below 5mm and is no more than 10mm C. The steel ball sinks more than 10 mm
[0092] [Vertical combustion evaluation] The polyurethane foams produced in the respective Examples and Comparative Examples were evaluated for vertical flammability according to the following procedures (1) to (3). (1) A rod-shaped sample with dimensions of 100 mm x 10 mm x 10 mm is cut out of the polyurethane foam to serve as a test specimen. (2) The lower end of the vertically held rod-shaped sample is brought into contact with a propane gas burner with a flame length of 20 mm. (3) The state of flame spread of the rod-shaped sample exposed to the flame in (2) above is evaluated.
[0093] <Vertical Combustion Evaluation Standard> A: Flame spread is less than 50 mm B: Flame spread is 50 mm or more and less than 100 mm C: Flame spread is 100 mm or more D. The flame is 100 mm or more in the expanded state and almost no combustion residue remains.
[0094] [Example 1] According to the formulation in Table 1, the polyol compound, catalyst, flame retardant, blowing agent, and foam stabilizer were weighed into a 1000 mL polypropylene beaker and stirred with a hand mixer at 20°C for 10 seconds to prepare a polyol composition. The polyol composition was then cooled to 10°C, and a polyisocyanate composition (polyisocyanate compound) adjusted to the same temperature of 10°C was added to prepare a foamable urethane resin composition, which was then stirred with a lab-di-spar for 3 seconds to prepare a polyurethane foam. The polyurethane foam was used to carry out the above-mentioned workability evaluation, hot steel ball evaluation, and vertical combustion evaluation. The total smoke generation, total heat generation, and maximum heat generation rate were also evaluated by the above-mentioned procedures. The various evaluation results are shown in Table 1.
[0095] [Examples 2 to 8, Comparative Examples 1 to 2] A polyurethane foam was obtained in the same manner as in Example 1, except that the formulation was changed as shown in Table 1. The polyurethane foam was used to carry out the above-mentioned workability evaluation, hot steel ball evaluation, and vertical combustion evaluation. In addition, the total smoke generation, total heat generation, and maximum heat generation rate were also evaluated by the above-mentioned procedures. The various evaluation results are shown in Table 1.
[0096] [Table 1]
[0097] As shown in each example, the polyurethane foam formed from the foamable urethane resin composition of the present invention was found to have low smoke properties, as evidenced by the low total smoke emission. In contrast, the polyurethane foams formed from the foamable urethane resin compositions of the comparative examples had a total smoke emission evaluation outside the range specified in the present invention, indicating that they were prone to generating smoke when burned.
Claims
1. A foamable urethane resin composition comprising a polyol compound, a polyisocyanate compound, a flame retardant, a foaming agent, and a catalyst, the polyol compound contains an aromatic polyester polyol, and the content of the aromatic polyester polyol is 50 parts by mass or more relative to 100 parts by mass of the polyol compound; the catalyst comprises a bismuth compound, an imidazole compound, and a quaternary ammonium salt; the flame retardant comprises tris(β-chloropropyl)phosphate; The polyurethane foam made of the foamable urethane resin composition was subjected to a cone calorie test in accordance with the ISO-5660 test method, and the total smoke emission was 500 m 2 / m 2 The following foamable urethane resin compositions (excluding those containing red phosphorus and a metal stannate in combination):
2. The foamable urethane resin composition according to claim 1 , wherein the catalyst comprises a trimerization catalyst.
3. The foamable urethane resin composition according to claim 1 or 2, which is substantially free of an inorganic filler.
4. 3. The foamable urethane resin composition according to claim 1, further comprising an inorganic filler, the inorganic filler being a brominated flame retardant.
5. The foamable urethane resin composition according to any one of claims 1 to 4, having an isocyanate index of 130 to 600.
6. The foamable urethane resin composition according to any one of claims 1 to 5, which is used for spray applications.
7. A polyurethane foam obtained by foaming the foamable urethane resin composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
Composition for low-smoking flame-retardant polyisocyanurate foam and low-smoking flame-retardantfoam prepared therefrom
JP1999140150A
Polyol composition, flame-retardant polyurethane resin composition, and their production
JP1999246754A
Use of trialkyl phosphate as a smoke suppressant in polyurethane foams
JP2014532098A
Flame retardant polyurethane foam
JP2015151524A
Polyurethane foam production method and polyurethane foam produced thereby
JP2016188330A